2020
DOI: 10.3390/ani10101912
|View full text |Cite
|
Sign up to set email alerts
|

Carcass Characteristics and Primal Pork Cuts of Gilts, Boars, Immunocastrates and Barrows Using AutoFOM III Data of a Commercial Abattoir

Abstract: The surgical castration of male piglets as a routine procedure in modern pig production is facing increasing societal criticism. Pork production with boars and immunocastrates are available alternatives, but both have low market shares as it is so far uncertain how the carcass characteristics and primal pork cuts of boars and immunocastrates will be estimated in comparison to barrows and gilts. This article therefore evaluates the impact of sex group (gilts, boars, immunocastrates and barrows) on carcass chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 43 publications
(72 reference statements)
1
5
0
Order By: Relevance
“…A similar trend was found for the percentage of pigs slaughtered in 2019 based on the data released by the Livestock Products Quality Assessment Service in 2019 [1]. These results were also similar to results of Kevin et al (2020) [35], where S, the highest grade of gilts, showed a higher ratio than that of barrows. Although pig carcass grade used in Europe differs from that in Korea in terms of meat production, the high proportion of the highest grade in gilts cannot be ignored.…”
Section: A C C E T E Dsupporting
confidence: 87%
See 2 more Smart Citations
“…A similar trend was found for the percentage of pigs slaughtered in 2019 based on the data released by the Livestock Products Quality Assessment Service in 2019 [1]. These results were also similar to results of Kevin et al (2020) [35], where S, the highest grade of gilts, showed a higher ratio than that of barrows. Although pig carcass grade used in Europe differs from that in Korea in terms of meat production, the high proportion of the highest grade in gilts cannot be ignored.…”
Section: A C C E T E Dsupporting
confidence: 87%
“…(2020) [35], gilts showed no significant difference value compared to barrows(p < 0.0001). Such differences in results between the study of Kevin et al (2020) [35] and the present study might be due to different breed of pigs used in the experiment. From results…”
Section: E T E Dmentioning
confidence: 85%
See 1 more Smart Citation
“…There are several no-destructive techniques for analyzing pig carcasses worldwide, including dual-energy x-ray absorptiometry [4], magnetic resonance imaging [5], computed tomography [6], infrared reflectance spectroscopy [7], and ultrasound imaging [8]. Dual-energy x-ray absorptiometry, magnetic resonance imaging, and computed tomography are more accurate than ultrasound imaging [9].…”
Section: Introductionmentioning
confidence: 99%
“…Dual-energy x-ray absorptiometry, magnetic resonance imaging, and computed tomography are more accurate than ultrasound imaging [9]. However, ultrasound imaging has advantages of being applicable to any carcass size with a reasonable price, no radiation, and real time measurement [8,9]. These techniques are important for performance testing, grading, and final selection or payment of meat-producing animals.…”
Section: Introductionmentioning
confidence: 99%